MAKROEKONOMI DAN STRUKTUR MODAL PADA PERUSAHAAN PERBANKAAN DI LQ45 - Putri Zahara; Candra Sigalingging (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
The development of an established company will continue to require funding, as will running business operations to obtain equity and profits. Companies that need development often have an impact on gaps or external conditions such as changes in economic values ​​that are unstable and cause inflation. As a result, financial companies must be aware of the impact of inflation, by paying attention to each financial component, in the best way, profit or profitability. But not only that, banking companies which are the bridge to the economy are required to create prosperity. The current funding process is based on capital and debt which are included in the capital structure, therefore this can be a strategic policy where the debt and equity financial structure can provide benefits in the certain periode of time. Using a ata set of 30 banking companies as objects in 2013 to 2022 and using panel data analysis techniques - fixed effect models. Where the research results show that capital, profits, assets and company value can be indicators of company finances in maintaining company stability despite economic turmoil.